Mechanical cell disruption of microorganisms - Kasyniuk, Maksym; Hrininh-Hera, Kateryna; Gubenia, Oleksii (My University, 2023)
The cell disruption on an industrial scale is employed during the extraction of beta-glucan from the shells of brewing yeast, the production of biofuel from microalgae, and the production of insulin from Escherichia coli bacterial cultures. On an industrial scale, cell disruption utilizes mechanical methods, particularly in bead mills and under pressure in gaps, aimed at disrupting the integrity of the cell wall. While chemical agents may serve as supplements to intensify the process, the ultrasonic method remains confined to the laboratory, as its application on an industrial scale is complicated by high energy costs and rapid equipment wear.
Keywords: bead; руйнування клітин мікроорганізмів; cell destruction; бісерний млин; кафедра мехатроніки та пакувальної техніки; кафедра машин і апаратів харчових та фармацевтичних виробництв